Heavy Metals and Pathogens in Leafy Vegetables - Goyal, Dinesh (My University, 2007)
Heavy metal and presence of bacterial pathogen in randomly collected samples and from agricultural areas in and around Patiala City was conducted. In palak (Beta vulgaris L), fenugreek (Trigonella foenum-graecum) and coriander (Coriandrum sativum) heavy metals Fe, Zn, Cd, Cr, Ni and Pb were analysed by wet digestion method and total bacteria and coliforms were enumerated on TSA (Tryptone Soya Agar) and VRBA (Violet Red Bile Salt Agar) media. All vegetables had metal content in the order Fe> Zn> Pb> Cr> Ni> Cd. Only 32% palak, 26% of coriander and 23% of fenugreek samples contained Pb concentration below the permissible limit of 2.5 mg/Kg as per Indian Standard of Food Adulteration Act (PFA), 1954. Among all green leafy vegetables nearly 67-76% of samples were high in Pb, 18-39% samples were high in Zn, which crossed Indian permissible limit of 50 mg/Kg, and 6-9% samples were high in Cd, which was beyond 1.5 mg/Kg. The results indicate that the consumers are purchasing vegetables with high level of heavy metals (HMs). The total bacterial count in vegetables ranged between 250-109 cfu x104 and 5.7-6.0 log cfu/g and coliforms were in the range of 29-87 cfu x 104 and 4.8-5.6 Log cfu/g, which is an indication of improper pre harvest and post harvest handling. The metal content in vegetables from agricultural areas indicate high levels of soil contamination and there is a potential danger of heavy metal accumulation particularly Pb and Cd in vegetables grown in vicinity of Main Village, Bahadurgarh, Sullar road, Khusropur, Bhanari and Thapar Technology Campus. Pot culture experiment showed that heavy metals were accumulated at high levels in these vegetables when irrigated with synthetic water containing high concentration of heavy metals.
Keywords: Pathogens in Leafy Vegetables; Bacterial Pathogens; Heavy Metals in Plant